2020
DOI: 10.1038/s41598-020-61589-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SNP Array Abnormalities in Patients with DE NOVO Acute Myeloid Leukemia with Normal Karyotype

Abstract: Nearly 50% of patients with de novo acute myeloid leukemia (AML) harbor an apparently normal karyotype (NK) by conventional cytogenetic techniques showing a very heterogeneous prognosis. this could be related to the presence of cryptic cytogenetic abnormalities (ccA) not detectable by conventional methods. The study of copy number alterations (CNA) and loss of heterozygozity (LOH) in hematological malignancies is possible using a high resolution SNP-array. Recently, in clinical practice the karyotype study has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Currently, chromosomal variations and gene mutations are considered the main factors in the pathogenesis of AML and are combined to assess the cytogenetic risk for prognostic prediction and treatment selection (Alharbi et al, 2013;Meyer and Levine, 2014;Döhner et al, 2017;Nagy et al, 2019). However, nearly 50% of AML patients harbor a normal karyotype, and some of them even lack common somatic mutations (Ibáñez et al, 2020). Thus, it is important to explore new potential factors with prognostic significance and/or roles in leukomogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, chromosomal variations and gene mutations are considered the main factors in the pathogenesis of AML and are combined to assess the cytogenetic risk for prognostic prediction and treatment selection (Alharbi et al, 2013;Meyer and Levine, 2014;Döhner et al, 2017;Nagy et al, 2019). However, nearly 50% of AML patients harbor a normal karyotype, and some of them even lack common somatic mutations (Ibáñez et al, 2020). Thus, it is important to explore new potential factors with prognostic significance and/or roles in leukomogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although molecular studies are becoming more and more essential for MDS diagnosis and stratification [ 2 ], SNP microarrays are valuable complementary techniques. An AML study using SNP microarrays showed that 50–100% of cases harboring deletions or ROH, in distinct myeloid genes, show point mutations of the same genes [ 13 ]. Detection of CNA and ROH is important, especially to determine the TP53 status in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of methods in addition to cytogenetics depends on several factorsresources of the diagnostic or clinical entity, number of patients, recruitment, equipment, financing, and/or the possibility and practice of outsourcing such services [5]. In Bulgaria, current national healthcare politics do not provide next-generation sequencing (NGS) or single nucleotide polymorphism (SNP)-array on patients with hematological malignancies so regardless of being the most highly esteemed methods in the developed world [6][7][8][9], they remain inaccessible for most in need. This issue creates a demand for an inexpensive, yet reliable and wide-ranging option with a short turnaround time (TAT).…”
Section: Introductionmentioning
confidence: 99%